ENGLISH STUDENTS’ DIFFICULTIES IN COMPLETING READING TOEFL SECTION AT EIGHT SEMESTER AT UNIVERSITAS JAMBI - Ratu Gairah Isma Gustin (Universitas Jambi, 2023)
This study aims to determine whether TOEFL reading skills are more difficult for English study program of students at Universitas Jambi, based on TOEFL reading skills given to students in the eighth semester at Universitas Jambi , and whether TOEFL reading skills are difficult for English Study Program students at Universitas Jambi. The data of this study were collected using mixed method, quantitative design with a survey study and qualitative design with a descriptive study approach involved 23 participants. The participants in this study were eight semester students at English study program in Universitas Jambi. This study used the data collection TOEFL reading test,TOEFL reading score, and interview. TOEFL reading test was used for describing students’ difficulty. Interview was used for investigating whether the students’ experience the difficulties or not. The TOEFL reading test and an interview were main instruments in this study. TOEFL reading score was a supplementary instrument that can assist the researcher in selecting the students who needed a low grade to be questioned. Firstly, the students’ experience the difficulty in reading section of TOEFL test such as lack of accuracy in reading, availability of time during test, and lack of vocabulary. Secondly, the result of this study showed that the ordering of difficulty items in TOEFL reading skills encompasses responding of transition questions (0.9), finding topic/main idea (0.21), finding specific information (0.21), and finding stated details (0.26).